+0

# Factoring

+1
41
3
+198

Factor this expression.

\(-2x^2+x+21=0\)

#1
+4478
+3

Hey! This is the same equation that you get from the last question.

You can solve it by factoring like this....

-2x2 + x + 21  =  0

Multiply the  -2  and  21  to get  -42  .

Now split the middle term with two numbers that add to  1  and multiply to  -42 .

-2x2 - 6x + 7x + 21  =  0

Factor a  -2x  out of the first two terms and a  7  out of the last two terms.

-2x(x + 3) + 7(x + 3)  =  0

Factor  a  (x + 3)  out of both remaining terms.

(x + 3)(-2x + 7)  =  0

hectictar  Sep 13, 2017
Sort:

#1
+4478
+3

Hey! This is the same equation that you get from the last question.

You can solve it by factoring like this....

-2x2 + x + 21  =  0

Multiply the  -2  and  21  to get  -42  .

Now split the middle term with two numbers that add to  1  and multiply to  -42 .

-2x2 - 6x + 7x + 21  =  0

Factor a  -2x  out of the first two terms and a  7  out of the last two terms.

-2x(x + 3) + 7(x + 3)  =  0

Factor  a  (x + 3)  out of both remaining terms.

(x + 3)(-2x + 7)  =  0

hectictar  Sep 13, 2017
#2
+198
+1

The other guy's answer really confused me because he didn't know how to use Latex, so I worked most of it out as best I could then asked this.

#3
+90162
0

Thanks Hectictar,